Nylon Hang Back Sutures in the Repair of Secondary Ptosis Following Overcorrected Dysthyroid Upper Eyelid Retraction. Issue 1 (January 2016) - Shah-Desai, Sabrina; Azarbod, Parham; Szamocki, Sonia; Rose, Geoffrey E.
Abstract : Purpose: Repair of blepharoptosis secondary to surgical overcorrection of thyroid related primary upper eyelid retraction (secondary ptosis) can be unpredictable. This study describes the long-term results of "hang-back" nylon sutures, for an anterior approach surgical repair of secondary ptosis. Methods: This was a retrospective consecutive case note review of patients referred with secondary ptosis (after prior upper eyelid lowering for thyroid eye disease), under the care of a single surgeon at Moorfields Eye Hospital & subsequently at Barking Havering Redbridge University Hospitals NHS Trust (SSD). In accordance with hospital trust policy, this audit was registered and all patient data was anonymized, ethical approval was not required. Patients with secondary ptosis underwent surgery under local anesthesia through an upper eyelid skin-crease incision. The anterior portion of the levator muscle was freed from all scar tissues and its action re-established on the superior part of the upper tarsal plate, using two 6-0 nylon hang-back sutures placed centrally and medially. The margin reflex distance 1 (MRD1), skin crease height, eyelid contour, symmetry of eyelid position (difference in margin reflex distance 1 <1 mm in both eyes) and degree of lagophthalmos were assessed from clinical notes preoperative and postoperatively at 1, 3, and 12 months. Results: Surgery was undertaken in 14 eyelids in 13 patients (3 males; 23%), with 9/14 (65%) eyelids having undergone attempted repair of ptosis prior to referral; in 7 of the 8 (88%) eyelids with previous failed ptosis repair, the referring surgeon had used soluble hang-back sutures. As compared with an average preoperative margin reflex distance 1 of 0.9 mm (median 1, range: −1 to 2 mm), the average margin reflex distance 1 at 3 months was 3.0 mm (median 3, range: 2.5–4 mm; p < 0.0001) and 2.8 mm at 12-month follow up (median 3, range: 2–4mm; p < 0.0001). The upper eyelid central skin crease height changed from a preoperative mean of 9.8 mm (median 9, range: 5–15 mm) to 8.7 mm at 3 months (median 8, range: 7–12 mm; p = 0.1412) and 8.9 mm at 12-month follow up (median 9, range: 7–11 mm; p = 0.2930). Only 3 patients had postoperative lagophthalmos (one patient 3 mm and two patients 1 mm) at 3 months after surgery, this resolving by the 12-month postoperative visit. Thirteen cases (93%) had a good functional, symmetrical, and aesthetic result at 12 month follow up, with a late recurrence of ptosis in 1 patient (7%). Conclusion: The "hang-back" semi-permanent suture technique for repair of over-corrected upper eyelid lowering in thyroid eye disease appears to provide an excellent and predictable long-term result with a low incidence of late recurrence of ptosis. Abstract : Nylon "hang-back" sutures appear to provide a stable long-term correction of secondary ptosis following overcorrected upper eyelid lowering for thyroid eye disease.